THE EFFECTIVENESS EXPLICIT INSTRUCTION METHOD TO IMPROVE STUDENTS’ ABILITY IN WRITING PROSEDURE TEXTS AT CLASS XI SMA NEGERI 2 LAWE BULAN ACADEMIC YEAR 2021/2022 - DHARAA YONITA; MUHAMMAD TAHIR; RAJA FAUZIAH (STKIP USMAN SAFRI KUTACANE, 2023)
This study deals with the effect of explicit instruction method in ability to make procedure text at class XI in SMA Negeri 2 Lawe Bulan Academic Year 2021/2022. Its objective is to find out whether the use explicit instruction has a significance effect in make procedure text. Population and samples used in this study were all students of class X total 36 students. The method used in this study is an experimental method with a one group as pre-test and post-test design. This study was carried on using quantitative method. The data was analysed by using t-test. The researcher found the pretest mean = 43,05 , deviation standard = 4,48 and experienced an increase in the posttest mean = 80,83, deviation standard = 4,55. From this analysis, writer found that guided explicit instruction method has significance in teaching writing procedure text. It can be proved by the result of the analysis showed that “ ” observed about 35,64 was higher than “ttable” about 2,030 with the level significance is 0,05% it implies that the teacher of English should use explicit instruction method in teaching make procedure text so that the teaching and learning process can be successful.